Constructing a German diaspora : the "Greater German Empire," 1871-1914 / by Stefan Manz. - Manz, Stefan (Routledge studies in modern European history., 2014)
This book takes on a global perspective to unravel the complex relationship between Imperial Germany and its diaspora. Around 1900, German-speakers living abroad were tied into global power-political aspirations. They were represented as outposts of a ""Greater German Empire"" whose ethnic links had to be preserved for their own and the fatherland's benefits. Did these ideas fall on fertile ground abroad? In the light of extreme social, political, and religious heterogeneity, diaspora construction did not redeem the all-encompassing fantasies of its engineers. But it certainly was at work,